Pengaruh Media Alat Bantu terhadap Keterampilan Passing Bawah Bolavoli pada Pembelajaran PJOK - Mohammad Zaim Zen; Ilmul Ma’arif; Rendra Wahyu Pradana; Guntum Budi Prasetyo (MAN Insan Cendekia Jambi, 2025)
This study aims to obtain information related to the effect of media tools on volleyball underhand passing. The method used is experimental research with a one-group pre-test post-test design, with a sample size of 65 students from junior high schools selected using purposive sampling. The procedure involved conducting a pre-test, treatment, post-test, and assessment of underhand passing using a modified Braddy Volley Ball Test. Data analysis was conducted using descriptive statistics and a paired T-test using SPSS calculations. The pre-test results fell into the poor category (46.16%). The post-test results fell into the good category (41.53%). Meanwhile, the difference test results showed that there was an effect on underhand passing skills based on the sig results. The conclusion is that teaching aids have a positive impact on volleyball underhand passing.